Integration of Linguistics, Mental Health & Wellness for Responsive Governance (African Journal of Public Administration & Management, 2026)
Effective governance requires linguistic inclusivity, mental health literacy, and wellness. Head teachers serve as cultural mediators in multilingual settings.These domains support holistic, human-centered school leadership.Mother tongue based and Multilingual Education (MTB-MLE) policy supports local languages but implementation challenges persist.Free education has contributed a % to this teacher stress thus increasing the need for psychosocial support.Few studies integrate language, mental health, and wellness in school governance.
Keywords: Mental Health & Wellness; Responsive Governance; Linguistics